Jurisdiction of courts over Islamic banking in Nigeria and Malaysia - Bello, Shafi‘i Abdul Azeez; Mohd Yasin, Norhashimah (Bangladesh Islamic Law Research and Legal Aid Centre, 2015)
Islamic finance is profit-oriented. However, it has moral and ethical values that are based on the Sharīah. Despite the roots of religiosity of its origins, its products are useful to all of mankind who are willing to be fair and just in their economic endeavours. However, the growth and development of an Islamic bank and the Islamic finance system depends upon institutions wherein its dispute resolutions are anchored. The institutions for Islamic finance dispute resolutions must house practitioners who are knowledgeable and versed in Islamic finance. In Nigeria, Islamic banking and finance (IBF) has proved to be the most developed system of profit and loss sharing banking based on non‐interest principles mainly due to its international recognition. On the other hand, Malaysia is one of the few exceptional jurisdictions where Islamic banking cases have been published in various law reports such as the Malayan Law Journal and the Current Law Journal. From 1987- 2010, there have been several Islamic banking cases which have been published in law reports, 20 of which have been famously quoted and referred to. This paper aims to explain the jurisdiction of the courts on Islamic banking and finance in Nigeria and Malaysia. It discusses the jurisdiction of the courts over banking in Nigeria generally, their hierarchy as well as jurisdiction over Islamic banking in the same. Similarly, the jurisdiction of the courts over IBF in Malaysia has been critically analysed. It has 1 Ph.D. Candidate, Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, Email: shafihyajadi@hotmail.com 2 Professor, Dr. Civil Law Department, Ahmad Ibrahim Kulliyyah of Laws, International Islamic University Malaysia, Email: norhashimah_iiu@yahoo.com.au 55 JOURNAL OF ISLAM, LAW AND JUDICIARY: 1 (3), 2015 been recommended in conclusion that the constitution should be amended in order to remove jurisdiction related to IBF from the sphere of the conventional courts for successful implementation of the IBF in the models studied.